Fractional ambiguity function: Properties and uncertainty inequalities in signal processing - Mawardi Bahri; Islah Audziah P.B.; Hatem Mejjaoli; Amran Rahim (Franklin Open, 2025)
This article presents the construction of the fractional ambiguity function by combining the definition of the ambiguity function and the kernel of the fractional Fourier transform. Several properties of the fractional ambiguity function are presented, which are an expansion of the corresponding properties of the classical ambiguity function. Further, some examples of signals for estimating the fractional ambiguity function are presented. Finally, based on the properties, an in-depth investigation of various versions of the uncertainty principles involving the fractional ambiguity function is investigated.